ACCOUNTING REGULATION AND ENFORCEMENT MECHANISMS: THE AUDITOR´S ROLE IN THE PORTUGUESE LISTED GROUPS - Fialho Silva, Ana (2016)
The purpose of this article is to examine the extent to which the clauses for the exclusion of subsidiaries from consolidation are used, in order to assess the degree of compliance with accounting regulation and the effectiveness of the statutory auditor as an enforcement mechanism in case of observed noncompliance. The presentation of consolidated financial statements by Portuguese companies was not regulated in detail before the implementation of the EU’s Seventh Directive and the general obligation to prepare consolidated accounts had not applied to Portuguese companies until 1991. Regulators have been responsible for the endorsement of accounting rules and managers ar responsible for the information disclosed by Portuguese companies regarding the scope of group accounting. In practice, the scope of consolidation depends on the judgment of makers and managers of the parent company. Auditors may play a key role in the process of guaranteeing the correct application of prevailing standards and thus encompassing the enforcement of accounting regulations and contributing to the quality of disclosed information. Our sample includes the consolidated financial statements of all the Portuguese companies listed in the Lisbon Stock Exchange on December 31st for the year 1999, to which the Official Accounting Plan is applicable. Our conclusion is that diversity exists among accounting practices regarding the adopted group concept and the use of the clauses for excluding subsidiaries from consolidation. The role of the auditors as enforcement actors seems to be minor, as we did find few qualifications in their audit reports in the cases of observed non-compliance with the accounting regulation.